Equity and trusts - TANG, Hang Wu (Institutional Knowledge at Singapore Management University, 2020)
Jocelyn Rita d/o Lawrence Stanley v Tan Gark Chong1 (“Jocelyn Rita v Tan Gark Chong”) is an example of an attempt to set aside a trust deed in the wake of BOM v BOK. 2 This case takes place in the context of a husband and wife relationship.